Brand Authenticity Dalam Perspektif Konsumen: Analisis Kualitatif Dan Regresi Logistik Ulasan Shopee Di Indonesia - Valdi Mughni Budiman; Dini Safitri; Ratu Chaterine Fajri; Winda Kartika (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The rapid growth of e-commerce in Indonesia has transformed the dynamics of consumer–brand relationships in digital environments. In such contexts, brand authenticity becomes a critical factor influencing consumer perception, trust, and evaluation. This study aims to analyze consumer perceptions of brand authenticity within the Shopee platform by integrating qualitative thematic analysis and quantitative logistic regression. The research employed a mixed-method approach using 2,937 Shopee user reviews consisting of review texts, ratings, and sentiment labels. Thematic analysis was conducted to identify dimensions of brand authenticity reflected in consumer narratives, while logistic regression was used to examine the influence of rating on sentiment polarity. The findings reveal that rating significantly affects the probability of positive sentiment. Furthermore, brand authenticity in Shopee is constructed through three dominant dimensions: credibility (consistency between product description and reality), integrity (transparency and system reliability), and continuity (consistency of user experience over time). The results indicate that authenticity in e-commerce is experience-based rather than solely identity-based, where user-generated reviews and ratings function as credibility signals under conditions of information asymmetry. This study contributes to the literature by extending the concept of brand authenticity into a digital marketplace context and provides practical implications for e-commerce platforms in managing system consistency, transparency, and consumer trust.